New and Emerging Targeted Therapies for Pediatric Acute Myeloid Leukemia (AML) - Jing Chen; Chana L. Glasser (MDPI AG, 2020)
The relapse rate for children with acute myeloid leukemia (AML) remains high despite advancements in risk classification, multi-agent chemotherapy intensification, stem cell transplantation, and supportive care guidelines. Prognosis for this subgroup of children with relapsed/refractory AML remains poor. It is well known that the ceiling of chemotherapy intensification has been reached, limited by acute and chronic toxicity, necessitating alternative treatment approaches. In the last several years, our improved understanding of disease biology and critical molecular pathways in AML has yielded a variety of new drugs to target these specific pathways. This review provides a summary of antibody drug conjugates (ADCs), small molecule inhibitors, and tyrosine kinase inhibitors with an emphasis on those that are currently under clinical evaluation or soon to open in early phase trials for children with relapsed/refractory AML.